Micropropagation of banana seedlings in liquid media - Andrade, Renata Aparecida de; Marques, Thaila Fujiwara; Jasper, Samir Paulo; Damatto Junior, Erval Rafael; Fuzitani, Eduardo Jun; Nomura, Edson Shigueaki (Comunicata Scientiae, 2011)
The banana is a fruit with a great economic importance, especially for the region of the "Vale do Ribeira", the largest producer in the State of Sao Paulo, Brazil. Seedlings growth is one of the main steps to be observed and performed with the utmost care to avoid contamination of materials and their proliferation in field conditions. Currently, the micropropagation technique has been used to obtain the seedlings, resulting in material free of pathogens, which gives greater security to the producer. The use of micropropagation results in higher cost of seedlings, what is compensated by the quality. One way to reduce the cost of this technique is reducing the amount of agar present in the culture medium. The objective of this research was to evaluate the response of banana to different compositions of culture medium, and the development of the seedlings. We have tested concentrations of agar: 0.0 (control), 1.2, 2.4, and 4.8 g L-1, mixed in MS medium, forming an experiment in 2 x 4 factorial scheme (cultivars x doses of agar ). After 25 days of transplant, we estimated the average plant height (cm), number and average length of roots (cm), dry mass of shoots and roots (g). Considering the results, we concluded that there is no need to use agar in the composition of the medium culture medium as for micropropagation of cultivars.